1996
DOI: 10.2175/106143096x127695
|View full text |Cite
|
Sign up to set email alerts
|

Fate of selected RCRA compounds in a pilot‐scale activated sludge system

Abstract: This research determined the removal and fate of 11 selected RCRA compounds in a pilot‐scale activated sludge system with a 4‐day SRT and 7.5‐hour HRT. Screened and degritted raw wastewater from a Cincinnati, OH, wastewater treatment plant was used for this study at the U.S. EPA's Test and Evaluation (T&E) Facility. A continuous feed of spike toxic cocktail of 0.25 mg/L each of acetone, methyl ethyl ketone, cyclohexanone, tetrahydrofuran, carbon tetrachloride, 1,1,1‐trichloroethane, 1,1,2‐trichloroethane, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

1998
1998
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 0 publications
1
11
0
Order By: Relevance
“…Acetone has a very low octanol/water partition coefficient, K ow , of 0.575 [21]. The observation that acetone is not greatly adsorbed onto suspended solids found here is in agreement with the reports in the literature [6,8,15,16]. The data obtained were used to describe the volatilization of acetone from this experiment, with a first-order rate (K v ) constant of 0.58 day −1 (r 2 = 0.66, data not shown).…”
Section: Acetone Removalsupporting
confidence: 92%
See 1 more Smart Citation
“…Acetone has a very low octanol/water partition coefficient, K ow , of 0.575 [21]. The observation that acetone is not greatly adsorbed onto suspended solids found here is in agreement with the reports in the literature [6,8,15,16]. The data obtained were used to describe the volatilization of acetone from this experiment, with a first-order rate (K v ) constant of 0.58 day −1 (r 2 = 0.66, data not shown).…”
Section: Acetone Removalsupporting
confidence: 92%
“…Eliosov et al [7] also investigated acetone removal from two different municipal treatment works activated sludges and found substantial removal. Bhattacharya et al [8] observed that the removal of acetone in a spiked toxic cocktail with other volatile organic compounds (VOC) in a pilot scale-activated sludge system. Yet, despite the overwhelming reports of acetone biodegradation, there is contradictory evidence to these reports.…”
Section: Introductionmentioning
confidence: 99%
“…Assumptions made for the plug flow model are (1) gas phase and liquid phase concentrations are uniform in the width direction; (2) there is no back mixing in the x direction for liquid or the z direction for gas; (3) liquid is well mixed in the z direction so that the liquid phase concentrations in the vertical plane of any position x are uniform; (4) drift of air bubbles with liquid is negligible, because the rise velocities of the bubbles are much higher than water flow; and (5) according to previous studies, [20][21][22] VOC removal by adsorption on the solids in aeration tanks is negligible; therefore, the major removal mechanisms that are considered include volatilization, biodegradation, and removal with the effluent; (6) the active biomass concentration is uniform throughout the tank; (7) the kinetics of VOC biodegradation is of the Monod type and can be further simplified to a first-order relationship to liquid phase concentration; and (8) the system is at steady state. Assumption 5 will result in an overestimation of the biodegradation rate constants.…”
Section: Methodsmentioning
confidence: 99%
“…Because industrial wastewater contains various organic compounds, the issue regarding emissions of the organic compounds from wastewater treatment plants (WWTPs) has been gradually emphasized (Mayer et al, 1994;Schmid et al, 2001;Lin and Chou, 2006;Oskouie et al, 2008). Over the past decade, numerous researchers developed a series of models to predict the fates of organic compounds in WWTPs (Ince and Inel, 1991;Parker et al, 1993;Hsieh et al, 1994;Melcer, 1994;Bhattacharya et al, 1996). However, these models only provided potential emission amounts of organic compounds under specific environmental conditions.…”
Section: Introductionmentioning
confidence: 99%